Thermodynamic and adhesive parameters of nanolayers in the system "metal-dielectric" - Yuzevych, V.M.; Koman, B.P.; Dzhala, R.M. (Functional Materials, 2018)
Evaluation technique of thermodynamic and adhesive parameters of interphase nanolayers in metal - insulator was developed by use of macroscopic methods of surface physics and thermodynamics methods of nonequilibrium processes. Typical parameters of interfacial interactions (interfacial energy, tension, density of electric charges, specific electrocapacity, electrical components of interfacial energy) for metals (Ag, Au, Cu, Fe) at Al₂O₃ interphase were calculated. It was found that increment of dielectric layer (Al₂O₃) surface tension which is accompanied with increasing of interfacial tensions and energies, electric component of the surface energy, specific surface charge of double electric layer and contact potential difference. The developed echnique can be used for evaluation of interfacial energy parameters of interaction between another physical nature composited pairs with aking into account the nature of the double electrical layer.